The Role of The Environmental Observer and The Environmental Police in Protecting the Environment in Iraqi Law: Comparative Legal Study - Mahdi Hamdi Mahdi; Hamad Kareem Hamad; Hind Abdulameer Hameed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The administration can follow different legal methods to protect and improve the environment which regulated by various environmental legislations, including preventive methods to prevent various activities from polluting the environment. That is by taking administrative control measures in accordance with its legal power and through its authority to issue disciplinary organizational and individual decisions. This is to impose forced execution if necessary. In order to protect the public order with its components (public security, public health and public tranquility), and this applies to environmental administrative control procedures. The administration has direct preventive methods (with direct impact) in this regard. Such as its authority to ban or license an activity, or to compel its owner to do a specific matter, or to be satisfied with merely reporting it. Others are indirect (with an indirect future impact), such as media, awareness and environmental education.